Ethnocultural Relations in the Republics of the Middle-Volga Region - Veronika J. Arestova (Publishing house "Sreda", 2021)
The information presented in the article describes the results of the sociological survey of ethnic and cultural relations in the Ethnic Republics of the Volga Federal District, namely the Chuvash Republic and the Mari El Republic. The purpose of the research was to highlight issues concerning some aspects of ethnic culture, specifically intercultural communication among young people (of 16-30 years old) in Cheboksary (the capital city of the Chuvash Republic) and Yoshkar-Ola (the capital city of the Mari El Republic). The research was focused on revealing the tolerant or intolerant, respectful or disrespectful attitude of native young people (representatives of the prevalent ethnicity) to other ethnic groups. The study was conducted using the methods of interviewing by means of computer-assisted web questionnaire. The answers were collected from university students. In conclusion, it was established that in general, native people from the Chuvash Republic and the Mari El Republic are non-conflict, tolerant and friendly.